Absorpsi CO2 Pada Wetted Wall Column dengan Variasi Laju Alir NaOH dan Konsentrasi Methyldiethanolamine - Purba, Elida; Simbolon , Rio Riski (Politeknik ATI Padang, 2023)
This research describes the biogas purification process by reducing CO 2 content using NaOH solution as an absorbent and methyldiethanolamine (MDEA) as a promoter in Wetted Wall Column (WWC). The purpose of this study was to determine the effect of MDEA concentration and flow rate of NaOH + MDEA solution on CO 2 absorption. The column is made of acrylic material with a diameter of 4.5 cm, height 50 cm, equipped with a tube with a diameter of 1.27 cm, height 45 cm. The tube is in the center of the column. The flow rate of absorbent solution for each run was varied as 150, 200, 250 and 300 ml/min and the concentration of MDEA for each run was 4% wt and 6% wt in 1 M NaOH. The biogas flow rate was 6 L/min, which was fed from the bottom of the column. The samples were analyzed by Gas Chromatography 2014 AT (SHIMADZU Corp 08128). The results showed that at 6% NaOH + MDEA solution, the solution flow rate of 150 mL/min was the best. Under these conditions, the output CO 2 content is 13.306% and the output CH4 content is 81.737%. The results of the output CO 2 content did not reach the 90% target because the biogas was contaminated by gas from the environment and the lack of control over the condition of the equipment during the absorption process.